Mythology : eyewitness companions - Wilkinson, Philip; Philip, Neil. (New York : Dorling Kindersley, 2007)
Tells the story behind famous tales, from Greek mythology to the lesser known myths from the Americas, Oceania and Africa. This work takes a fresh look at the great stories, epics, and legends of the past.
Includes index.
Keywords: Mythology